Future internet: The Internet of Things - Lu Tan; Neng Wang (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
Nowadays, the main communication form on the Internet is human-human. But it is foreseeable that in a near soon that any object will have a unique way of identification and can be addressed so that every object can be connected. The Internet will become to the Internet of Things. The communicate forms will expand from human-human to human-human, human-thing and thing-thing (also called M2M).This will bring a new ubiquitous computing and communication era and change people's life extremely. Radio Frequency Identification techniques (RFID) and related identification technologies will be the cornerstones of the upcoming Internet of Things (IOT).This paper aims to show a skeleton of the Internet of Things and we try to address some essential issues of the Internet of Things like its architecture and the interoperability, etc. At the beginning we describe an overview of the Internet of Things. Then we give our architecture design proposal of the Internet of Things and then we design a specific the Internet of Things application model which can apply to automatic facilities management in the smart campus. At last, we discuss some open questions about the Internet of Things.